Peran dan Makna Ritual Nyambai dalam Pelestarian Nilai Adat dan Identitas Budaya Masyarakat Lampung - Azzahra, Ladya; Kariswan, Kariswan; Sari, Lisa Retno (Department of Anthropology, 2025)
The Nyambai ritual represents one of Lampung's distinctive cultural heritages that embody local customs, belief systems, and social cohesion. This study aims to explore the Nyambai ritual as a traditional practice that contributes to the preservation of cultural values, ancestral veneration, and collective identity among Lampung communities. Adopting a qualitative approach, this research employs a literature review method based on journal publications from 2015 to 2025. Data were analyzed using a qualitative content analysis technique through stages of data collection, reduction, and interpretation. Findings reveal that the Nyambai ritual encapsulates essential social values such as social harmony, respect for ancestors, adherence to local norms, spirituality, and cultural identity formation. Moreover, this ritual demonstrates adaptive dynamics in response to social and environmental transformations, enabling the community to innovate while maintaining the authenticity of tradition. The active involvement of younger generations ensures the continuity of Nyambai as a medium for intergenerational knowledge transmission. Consequently, the Nyambai ritual functions not only as a cultural and spiritual expression that connects the community with their ancestors and nature but also as a symbol of Lampung identity amid contemporary changes. Abstrak: Ritual Nyambai merupakan salah satu warisan budaya khas masyarakat Lampung yang merefleksikan sistem kepercayaan, nilai sosial, dan tatanan adat setempat. Penelitian ini bertujuan untuk menganalisis ritual Nyambai sebagai praktik tradisional yang berperan dalam pelestarian nilai budaya, penghormatan kepada leluhur, serta penguatan identitas kolektif masyarakat Lampung. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan yang bersumber dari publikasi ilmiah periode 2015–2025. Analisis data dilakukan melalui tahapan pengumpulan, reduksi, serta interpretasi data menggunakan teknik analisis isi kualitatif. Hasil penelitian menunjukkan bahwa ritual Nyambai mengandung nilai-nilai sosial penting seperti keharmonisan masyarakat, penghormatan terhadap leluhur, kepatuhan pada norma adat, spiritualitas, serta pembentukan identitas budaya. Selain itu, ritual ini menunjukkan dinamika dan adaptasi terhadap perubahan sosial dan lingkungan tanpa menghilangkan esensi tradisi. Keterlibatan aktif generasi muda menjadi faktor kunci dalam menjamin keberlanjutan ritual ini sebagai wahana pewarisan nilai budaya. Dengan demikian, ritual Nyambai tidak hanya berfungsi sebagai praktik budaya dan ekspresi spiritual, tetapi juga menjadi simbol identitas Lampung di tengah arus modernitas yang terus berkembang.